Optimal Strategy for Antiplatelet Therapy After Coronary Drug-Eluting Stent Implantation in High-Risk “TWILIGHT-like” Patients With Diabetes Mellitus - Wang, Hao-Yu; Cai, Zhong-Xing; Yin, Dong; Song, Wei-Hua; Feng, Lei; Gao, Run-Lin; Yang, Yue-Jin; Dou, Ke-Fei (Frontiers in Cardiovascular Medicine, 2020)
Background: Patients with diabetes mellitus (DM) are known to be at high-risk for both ischemic and bleeding complications post-percutaneous coronary intervention (PCI). The ischemic benefit versus bleeding risk associated with extended dual antiplatelet therapy (DAPT) in high-risk “TWILIGHT-like” patients with diabetes mellitus after PCI has not been established. Methods: All consecutive high-risk patients fulﬁlling the “TWILIGHT-like” criteria undergoing PCI from January 2013 through December 2013 were identified from prospective Fuwai PCI Registry. High-risk "TWILIGHT-like" patients were defined by at least 1 clinical and 1 angiographic feature based on TWILIGHT trial selection criteria. The present analysis evaluated 3425 diabetics patients with concomitant high-risk angiographic features who were event-free at 1 year after PCI. Median follow-up was 2.4 years. The primary effectiveness endpoint was a composite of death, myocardial infarction, or stroke (termed major adverse cardiac and cerebrovascular events) and primary safety endpoint was clinically relevant bleeding according to Bleeding Academic Research Consortium type 2, 3, or 5. Results: On inverse probability of treatment weighting (IPTW) analysis, prolonged-term (>1-year) DAPT with aspirin and clopidogrel decreased the risk of primary effectiveness endpoint compared with shorter (≤1-year) DAPT (1.8% vs. 4.3%; hazard ratio [HR]IPTW: 0.381; 95% confidence interval [CI]: 0.252-0.576; P<0.001) and reduced cardiovascular death (0.1% vs. 1.8%; HRIPTW: 0.056 [0.016-0.193]). Prolonged DAPT was also associated with a reduced risk of definite/probable stent thrombosis (0.2% vs. 0.7%; HRIPTW: 0.258 [0.083-0.802]), and non-significantly lower rate of myocardial infarction (0.5% vs. 0.8%; HRIPTW: 0.676 [0.275-1.661]). There was no significant difference between groups in clinically relevant bleeding (1.1% vs. 1.1%; HRIPTW: 1.078 [0.519-2.241]; P=0.840). Similar results were observed in multivariable Cox proportional hazards regression model. Conclusion: Among high-risk PCI patients with diabetes mellitus without an adverse event through 1 year, extending DAPT>1-year significantly reduced the risk of major adverse cardiac and cerebrovascular events without an increase in clinically relevant bleeding, suggesting that such high-risk diabetic patients may be good candidates for long-term DAPT.